A New Approach for Three Phase Rectification with Minimum Measurement and Computational Requirements for Wind Power Applications - Mesbah, Mohsen; Mohseni, Mansour; Islam, Syed; Masoum, Mohammad Sherkat (Engineers Media Pty, 2011)
A new approach for AC-DC power conversion with fast dynamic response is proposed, which is based on instantaneous DC-side current demand. The reference current with negligible transients is achieved in a single switching period under balanced and unbalanced source voltage conditions. Unlike conventional AC-DC systems, the output DC voltage can be higher or lower than the maximum value of the input voltage. In the buck operating mode, smaller voltage rating of switches can be selected and high voltage supplies can operate with low voltage switches. As the high frequency current harmonics are minimal, there is no need to use ferrite cores or high frequency inductors. This results in a simple product that is particularly suitable for high power applications. As the only measurements in the AC side are the three-phase currents, the phase-locked loop circuit is eliminated, computation time is reduced and high sampling rates are not required. The unique features of this new approach make it a viable solution for the grid-side converter in doubly-fed induction generators for wind power applications. Simulations results are compared to a direct power control rectifier to show the feasibility of this new approach as a power source converter.